Oligoneuria (Yawari) anatina sp. nov. (Ephemeroptera: Oligoneuriidae) from the extreme north of Brazil - Massariol, Fabiana Criste; Cruz, Paulo Vilela (Zootaxa, 2015)
Oligoneuria (Yawari) anatina sp. nov. is described and illustrated based on nymphs and imagoes collected in the municipality of Serra do Navio, state of Amapá, Brazil. The main characteristics that can be used to distinguish the new species from other species of the genus are, in imagoes: 1) forewing with spectral cross veins between IRS and MP2 (male) or between IRS and IMP (female), 2) posterior margin of styliger plate distally rounded and with paired rounded projections; in nymphs: 1) vertex of head with two pairs of tubercles, 2) lateral margin of anterior projection of head straight. Cytochrome Oxidase subunit I (COI) sequences were used to associate male imago and immature stages of the new species.